Extension of Data Envelopment Analysis with Preference Information (Value Efficiency) - Joro, Tarja (Springer, 2015)
To improve performance is one of the key issues for managers in organizations. Demands to make operations more profitable and compatible as well as to cut public expenditure have been repeatedly present in headlines. The “goodness” of operations or performance is often simply measured in money; the firm making most money or the public sector unit having the least expenditure is considered to be the best one. However, the monetary measures do not always capture all aspects of the performance. Especially in the public sector it may be practically—or politically—impossible to attach prices to some goods or services produced: what is the price of a university degree, or of a medical operation saving a human life? We may be able to figure out the short-term costs of some operations, but what is— for instance—the price of the lost opportunity? How expensive it is not to educate, or to lose a life? Thus performance is clearly multidimensional in its nature, and several indicators (outputs) are required to characterize all essential aspects of performance. The factors (inputs) affecting performance are multidimensional as well. In practice, the relationships between outputs and inputs are often complex or unknown making direct performance evaluation a complicated task....